ANALYSING THE IMPACT OF SANDBOX REGULATION ON FINTECH INNOVATION AND FINANCIAL INCLUSION - Gunawan Widjaja (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Sandbox regulation has become an important instrument in driving innovation in the fintech sector while strengthening financial inclusion. By providing a controlled testing environment, it allows fintech companies to develop new technologies without facing excessive regulatory barriers. Through this approach, the sandbox opens up opportunities for the development of more efficient, adaptive, and relevant financial services for various segments of society, especially those who previously had difficulty accessing formal financial services. Its impact on financial inclusion is also significant, with sandbox regulation helping to reach underserved groups through products and services such as digital payments, microfinance, and peer-to-peer platforms. This contributes to improving financial literacy and expanding access to financial services, thereby reducing the financial gap. This regulation essentially promotes the development of a more inclusive and sustainable financial ecosystem. However, sandbox regulation is not without challenges. The need to establish a strong supervisory mechanism is important to maintain the balance between innovation and consumer protection and financial system stability. Therefore, the sustainability of sandbox effectiveness depends on close collaboration between regulators, industry players, and other stakeholders to create regulations that are adaptive and harmonious with technological developments.